Congenital intestinal fibrosarcoma with rapid recurrence requiring adjuvant chemotherapy. Issue 6 (24th April 2017) - See, Wing Shan Queenie; Cheuk, Daniel Ka Leung; To, Ka Fai; Ip, Philip Pun Ching; Chiang, Alan Kwok Shing; Ha, Shau Yin; Chan, Godfrey Chi Fung
Abstract: A total of 16 cases of congenital fibrosarcoma have been reported from 1975 to March 2015. Five of the 16 had abnormal fusion between erythroblast transformation specific translocation variant 6 and neurotrophin recptor gene neurotrophic tyrosine kinase, receptor, type 3 ( ETV6–NTRK3 ); in another five out of 16 this was absent, and six were not tested. All were managed by surgical resection but none involved metastasis. Herein we report the case of a newborn baby girl with congenital fibrosarcoma negative for ETV6–NTRK3 gene fusion, who presented with ileal perforation and positive resection margin. She had rapid recurrence with lymph node metastasis treated with postoperative chemotherapy. There was no further recurrence at >3 years of follow up.